KEBIJAKAN PEMERINTAH DALAM PENETAPAN UPAH MINIMUM - Sudiarta, Kadek; Wyasa Putra, Ida Bagus (Kertha Negara : Journal Ilmu Hukum, 2015)
In the article 27 paragraph 2 of the constitution 1945 each citizenship have right on working and proper life for human. Hence development at labour field is one of them designed to improve worker prosperity so that able to move business development. One of effort to move it is improvement on minimum wage that adjusted with economic condition and development. In its implementation determination of minimum wage not yet accommodate the companies at sector that able to pay more so that it can delay improvement of worker prosperity. In Indonesia which follow Pancasila industrial relationship can not universally to determine wage level, but can not ignore it. Because the government through many mechanism and rule will continue arrange and control of wage level. As the purpose for knowing the intention of the enactment of minimum wage along with government regulation is the basis of authority in setting the minimum wage as well as understand how the process of setting a minimum wage. Approach method in this article is normative juridical approach. The result showed that protection of wage through government policy on minimum wage still need as safety net toward protection of labor that is as anticipate step in order to obligation wage paid as according to minimum wage standard applied.
Keywords: Policies, Minimum Wage Fixing, Welfare Workers